Advances towards understanding long chain fatty acids-induced inhibition and overcoming strategies for efficient anaerobic digestion process. (15th February 2021) - Elsamadony, Mohamed; Mostafa, Alsayed; Fujii, Manabu; Tawfik, Ahmed; Pant, Deepak
Highlights: LCFAs-inhibition found to be saturation index, temperature, and concentration dependent. Syntrophus, Syntrophothermus, Syntrophomonas and Thermosyntropha can degrade LCFAs. Cations supplementation catalyzed LCFA salt formation. Natural adsorbents can enhance AD process via LCFAs capture. Abstract: The inhibition of the anaerobic digestion (AD) process, caused by long chain fatty acids (LCFAs), has been considered as an important issue in the wastewater treatment sector. Proper understanding of mechanisms behind the inhibition is a must for further improvements of the AD process in the presence of LCFAs. Through analyzing recent literature, this review extensively describes the mechanism of LCFAs degradation, during AD. Further, a particular focus was directed to the key parameters which could affect such process. Besides, this review highlights the recent research efforts in mitigating LCFAs-caused inhibition, through the addition of commonly used additives such as cations and natural adsorbents. Specifically, additives such as bentonite, cation-based adsorbents, as well as zeolite and other natural adsorbents for alleviating the LCFAs-induced inhibition are discussed in detail. Further, panoramic evaluations for characteristics, various mechanisms of reaction, merits, limits, recommended doses, and preferred conditions for each of the different additives are provided. Moreover, the potential for increasing the methane production via pretreatment using those additives are discussed. Finally, we provide future horizons for the alternative materials that can be utilized, more efficiently, for both mitigating LCFAs-based inhibition and boosting methane potential in the subsequent digestion of LCFA-related wastes. Graphical abstract: Image, graphical abstract